Genetic Association and Expression Correlation between Colony-Stimulating Factor 1 Gene Encoding M-CSF and Adult-Onset Still’s Disease - Yi-Ming Chen; Wei-Ting Hung; Wan-Chun Chang; Chia-Wei Hsieh; Wen-Hung Chung; Joung-Liang Lan; Ning-Rong Gung; Yun-Shien Lee; Der-Yuan Chen; Shuen-Iu Hung (Journal of Immunology Research)
Adult-onset Still’s disease (AOSD) is a rare and inflammatory disorder characterized by spiking fever, rash, arthritis, and multisystemic involvement. HLA has been shown to be associated with AOSD; however, it could not explain the innate immunity and autoinflammatory characteristics of AOSD. To assess the genetic susceptibility of AOSD, we conducted a genome-wide association study (GWAS) on a cohort of 70 AOSD cases and 688 controls following a replication study of 36 cases and 200 controls and meta-analysis. The plasma concentrations of associated gene product were determined. The GWAS, replication, and combined sample analysis confirmed that SNP rs11102024 on 5′-upstream of CSF1 encoding macrophage colony-stimulating factor (M-CSF) was associated with AOSD (P=1.20×10-8, OR (95% CI): 3.28 (2.25~4.79)). Plasma levels of M-CSF increased in AOSD patients (n=82, median: 9.31 pg/mL), particularly in the cases with activity score≥6 (n=42, 10.94 pg/mL), compared to the healthy donors (n=68, 5.31 pg/mL) (P<0.0001). Patients carrying rs11102024TT genotype had higher M-CSF levels (median: 20.28 pg/mL) than those with AA genotype (6.82 pg/mL) (P<0.0001) or AT genotype (11.61 pg/mL) (P=0.027). Patients with systemic pattern outcome were associated with elevated M-CSF and frequently observed in TT carriers. Our data suggest that genetic variants near CSF1 are associated with AOSD and the rs11102024 T allele links to higher M-CSF levels and systemic outcome. These results provide a promising initiative for the early intervention and therapeutic target of AOSD. Further investigation is needed to have better understandings and the clinical implementation of genetic variants nearby CSF1 in AOSD.